IMPLEMENTATION OF AUTHENTIC ASSESSMENT IN THE 2013 CURRICULUM AT SMA PMT PROF. DR. HAMKA PADANG - Diki Atmarizon; Novita Efendi (Ta'dib, 2019)
This research aims to describe the implementation of authentic assessment of 2013 curriculum at SMA PMT Prof. Dr. Hamka Padang. The descriptions were the kinds of assessment, the implementation of assessment and the problem encountered by the teachers. Participants were two English teachers and 7 students as the representative chosen purposively. This is descriptive research. The data were obtained from the instruments used which were observation checklist and interview guideline. The data were analyzed quantitatively and qualitatively. The result shows that 52,5% of assessment was  implemented by all English teachers. The numbers of the students became main problems besides basic knowledge, overburdened of time and classroom management. In short, the English teachers’ assessment belonged to ‘Fair’ category. Consequently, the assessment training and workshop should be followed by the teachers. Furthermore, the researcher can widen research to know the assessment implemented by English teachers of the 2013 curriculum.